2019
DOI: 10.1111/tbed.13320
|View full text |Cite
|
Sign up to set email alerts
|

Two novel recombinant porcine reproductive and respiratory syndrome viruses belong to sublineage 3.5 originating from sublineage 3.2

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is an agent of porcine reproductive and respiratory syndrome (PRRS), which causes substantial economic losses to the swine industry. PRRSV displays rapid variation, and five lineages coexist in mainland China. Lineage 3 PRRSVs emerged in mainland China in 2005 and prevailed in southern China after 2010. In the present study, two lineage 3 PRRSV strains, which are named SD110‐1608 and SDWH27‐1710, were isolated from northern China in 2017. To explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
(51 reference statements)
1
13
0
Order By: Relevance
“…The dramatic increase in the recombination rate since 2015 may be attributable to the wide spread of NADC30-like strains (Figure 2; Yu et al, 2012;Sui et al, 2018;Zhou et al, 2018a,c;. It was difficult to identify the characteristic regions of recombination in the PRRSV genome in this research and other studies (Yuan et al, 1999;Wang L. J. et al, 2016;Liu et al, 2017;Zhou et al, 2018b,c;Zhang W. L. et al, 2019). Evidences showed that recombination can changefv PRRSV virulence.…”
Section: Discussionmentioning
confidence: 70%
“…The dramatic increase in the recombination rate since 2015 may be attributable to the wide spread of NADC30-like strains (Figure 2; Yu et al, 2012;Sui et al, 2018;Zhou et al, 2018a,c;. It was difficult to identify the characteristic regions of recombination in the PRRSV genome in this research and other studies (Yuan et al, 1999;Wang L. J. et al, 2016;Liu et al, 2017;Zhou et al, 2018b,c;Zhang W. L. et al, 2019). Evidences showed that recombination can changefv PRRSV virulence.…”
Section: Discussionmentioning
confidence: 70%
“…Since PRRSV was first discovered in China in 1996 (An et al, ), imported viruses have had a strong impact on the country's pig industry. QYYZ‐like (lineage 3) strains of PRRSV, which are considered to have been imported from the Taiwan area and adapted to mainland China, are responsible for PRRS epidemics since 2010 in southern China (Gao et al, ; Zhang, Zhang, et al, ). In 2012, the NADC30‐like (lineage 1.8) virus was reported to have been imported into mainland China from North America, leading to pandemics in large areas of China between 2014 and 2016 (Li et al, ; Zhao et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, previously studies have suggested that the NADC30‐like virus is characterized by high‐frequency recombination with other lineage strains including the field virus and vaccine strains (Liu et al., 2017a; Liu et al 2019; Wang et al., 2018; Zhang et al., 2016; Zhao et al., 2015; Zhou et al., 2017). Of note, recombination events between lineage 3 virus and other lineage virus have emerged in China since 2010 (Chen et al., 2018; Lu et al., 2015; Liu et al, 2019; Zhang et al., 2017; Zhang et al., 2019; Zhou, Kang, Zhang, et al., 2018). In this light, it is not surprising that a high frequency of mutations and recombination with other lineage 1/lineage 3 strains may result in the emergence of new PRRSV variants.…”
Section: Discussionmentioning
confidence: 99%